Effect of a Mediterranean Diet Intervention on Dietary Glycemic Load and Dietary Glycemic Index: The PREDIMED Study - Ana Isabel Rodríguez-Rejón; Itandehui Castro-Quezada; Cristina Ruano-Rodríguez; María Dolores Ruiz-López; Almudena Sánchez-Villegas; Estefanía Toledo; Reyes Artacho; Ramón Estruch; Jordi Salas-Salvadó; María Isabel Covas; Dolores Corella; Enrique Gómez-Gracia; et al. (Journal of Nutrition and Metabolism)
Objective. To compare the one year effect of two dietary interventions with MeDiet on GL and GI in the PREDIMED trial. Methods. Participants were older subjects at high risk for cardiovascular disease. This analysis included 2866 nondiabetic subjects. Diet was assessed with a validated 137-item food frequency questionnaire (FFQ). The GI of each FFQ item was assigned by a 5-step methodology using the International Tables of GI and GL Values. Generalized linear models were fitted to assess the relationship between the intervention group and dietary GL and GI at one year of follow-up, using control group as reference. Results. Multivariate-adjusted models showed an inverse association between GL and MeDiet + extra virgin olive oil (EVOO) group: β = −8.52 (95% CI: −10.83 to −6.20) and MeDiet + Nuts group: β = −10.34 (95% CI: −12.69 to −8.00), when comparing with control group. Regarding GI, β = −0.93 (95% CI: −1.38 to −0.49) for MeDiet + EVOO, β = −1.06 (95% CI: −1.51 to −0.62) for MeDiet + Nuts when comparing with control group. Conclusion. Dietary intervention with MeDiet supplemented with EVOO or nuts lowers dietary GL and GI.